2012
DOI: 10.1186/2191-2858-2-24
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-assisted polystyrene sulfonate-catalyzed synthesis of novel pyrroles

Abstract: BackgroundPyrroles are widely distributed in nature and important biologically active molecules. The reaction of amines with 2,5-dimethoxytetrahydrofuran is a promising pathway for the synthesis of pharmacologically active pyrroles under microwave irradiation.ResultsMicrowave-induced polystyrenesulfonate-catalyzed synthesis of pyrroles from amines and 2,5-diemthoxytetrahydrofuran has been accomplished with excellent yield. This method produces pyrroles with polyaromatic amines.ConclusionThe present procedure f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…In this context, development of synthetic methods under solventless condition or the replacement of hazardous solvents with environmentally benign solvents, such as water, has become an important and popular research topic in recent years. The authors' laboratory has been actively engaged in developing green synthetic protocols for a long time [59,[63][64][65][66][67][68][69][70][71][72]. We have tested this present ecofriendly route for the synthesis of quinoxalines with different solvents as well as under solvent-free conditions.…”
Section: Chemistrymentioning
confidence: 96%
“…In this context, development of synthetic methods under solventless condition or the replacement of hazardous solvents with environmentally benign solvents, such as water, has become an important and popular research topic in recent years. The authors' laboratory has been actively engaged in developing green synthetic protocols for a long time [59,[63][64][65][66][67][68][69][70][71][72]. We have tested this present ecofriendly route for the synthesis of quinoxalines with different solvents as well as under solvent-free conditions.…”
Section: Chemistrymentioning
confidence: 96%
“…To exemplify, N-arylpyrroles (35) e Fig. 5, have been prepared in a reaction of 2,5-dimethoxytetrahydrofuran with a variety of amines, (aromatic, aliphatic, polyaromatic and heteropolyaromatic amines) in aqueous solution and using pole(styrene sulfonate) as a catalyst [83]. Due to the simplicity of the procedure, the products are easily isolated and, in this case, can be directly tested for anticancer activity.…”
Section: Development Of New Compounds From Commonly Available Reagentsmentioning
confidence: 99%
“…Shin-ichi Naya et al 63 Many authors [64][65][66][67] reported another approach to transformation of 2,5-dimethoxytetrahydrofuran to pyrrole derivatives 65 in presence of acid either by stirring at room temperature 64 , using microwav 65,66 or ultrasound conditions 67…”
Section: From Furan Derivativesmentioning
confidence: 99%